Editorial [Hot topic: In Vitro Imaging (Guest Editors: Flora Tang and Jinghai J. Xu)] - Tang, Flora; Xu, Jinghai J. (Combinatorial Chemistry & High Throughput Screening, 2009)
In the past decade, in vitro cell-based imaging has benefited from the maturing of automated devices and the advancement in image analysis tools. Applications of high content screening (HCS) have impacted both drug discovery and basic research in pharmaceutical industry and academic institutes. In this special issue dedicated to In Vitro Imaging, we are privileged to have some of the most distinguished movers and shakers of this field sharing their past experiences and their forward-thinking innovative development. This special thematic issue is divided into 3 sections. The first section includes practical applications and impact of HCS in Drug Discovery; and innovative new development, which will certainly impact the advancement of in vitro imaging.